A copy of the Celestial Globe of Ferdinand Verbiest SJ at Leuven University (Belgium): As symbol of friendship and exchange between China and Europe (The Macau Ricci Institute Journal, 2023)
In the year 1675, at the request of Emperor Kangxi, Ferdinand Verbiest drew the plans for six bronze astronomical instruments that stand till today on top of the Ancient Observatory in Beijing. The most remarkable of them is the Celestial Sphere. This happened at the peak of the friendly exchange between the Jesuits and China initiated by Matteo Ricci, Adam Schall von Bell and Ferdinand Verbiest during the 17th and 18th centuries which are the golden period of the relations of China with the West. The Opium Wars during the 19th century and theBoxer Rebellion in 1900 destroyed all that. Th astronomical instruments witnessed this historical drama which makes them witnesses of the good and bad times of East-West relations.That fact inspired the Ferdinand Verbiest Foundation of Leuven University (Belgium) to order a perfect bronze copy of the Celestial Globe, manufactured in Beijing. From Leuven University the copy of the Celestial Sphere tells the world today to restore the old relationship of equality, mutual respect, and friendship between East and West.